2008
DOI: 10.1007/s00383-008-2181-1
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of outcome of anorectal anomaly in childhood: the role of anorectal manometry and endosonography

Abstract: The aim of this study was to evaluate role of anorectal manometry (ARM) and anal endosonography (ES) in assessment of the internal anal sphincter (IAS) quality on continence outcome following repair of anorectal anomalies (ARA). We devised a scoring system to evaluate the quality of the IAS based on ARM and ES and correlated the scores with clinical outcome, using a modified Wingfield score (MWS) for faecal continence. We also assessed the implication of megarectum and neuropathy on faecal continence. Of 54 ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
32
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 47 publications
(89 reference statements)
1
32
0
Order By: Relevance
“…High-ARM patients had the lowest RP, with mean RP of 17 ± 7.7 and 21 ± 9.4 mm of Hg in infants and children group, respectively, thus explaining the reason for the poor clinical outcome in patients with high ARM owing to shorter sphincteric length and poor resting tone of anal canal. Similar observations of RP in ARM patients have been reported from other centers [12,15,16]. Anorectal sensory receptors reside either in rectum or in the pelvic floor.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…High-ARM patients had the lowest RP, with mean RP of 17 ± 7.7 and 21 ± 9.4 mm of Hg in infants and children group, respectively, thus explaining the reason for the poor clinical outcome in patients with high ARM owing to shorter sphincteric length and poor resting tone of anal canal. Similar observations of RP in ARM patients have been reported from other centers [12,15,16]. Anorectal sensory receptors reside either in rectum or in the pelvic floor.…”
Section: Discussionsupporting
confidence: 81%
“…Both modalities can identify focal defects and scarring in the anal sphincters and thus provide valuable information [8,9], but these investigations do not address defect in anorectal function and have relative strengths and weaknesses [10]. Manometric assessment has been the principal method to obtain objective data of postoperative sphincter function [11][12][13]. We had obtained our own normative data of anorectal manometry in healthy children of different age groups [3] that helped us to compare our results of anorectal manometry in our patients with ARM in present study.…”
Section: Discussionmentioning
confidence: 99%
“…The resting pressure depends on the constant state of contraction if the IAS at rest (85%) and partially on the EAS (15%), whereas the squeezing pressure is generated by the voluntary contraction of the EAS. A positive RAIR indicates good activity of the IAS, whereas its absence correlates well to a deficiency or scarring of the sphincter [13]. Anorectal manometry requires patient cooperation for a complete evaluation of sphincter function, which is why we only enroll children older than 4 years and with no mental impairment for this type of evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…Their study demonstrated a significant correlation between the endosonographic findings, the manometric data, and the grade of continence in both groups. Keshtgar et al [13] performed anorectal manometry under ketamine anesthesia, and therefore, their evaluations were limited to the functional characteristics of the IAS. These authors underlined how the integrity of the IAS and an adequate aARP (N30 mm Hg) were necessary to assure a good continence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation